Review of trans-Mediterranean power grid interconnection: A regional roadmap towards energy sector decarbonization - Yu, Kaifeng; van Son, Paul (Global Energy Interconnection, 2023)
Climate change is becoming an important issue in all fields of infrastructure development. Electricity plays a core role in the decarbonized energy system’s path to a regional zero-emission pattern. A well-built trans-Mediterranean backbone grid can hedge the profound evolution of regional power generation, transmission, and consumption. To date, only Turkey and the Maghreb countries (i.e., Morocco, Algeria, and Tunisia) are connected with the Continental European Synchronous Area. Other south- and east-shore countries have insufficient interconnection infrastructures and synchronization difficulties that have proven to be major hurdles to the implementation of large-scale solar and wind projects and achievement of climate goals. This study analyzes the current trans-boundary grid interconnections and power and carbon emission portfolios in the Mediterranean region. To align with the recently launched new climate target ‘Fit for 55’ program and the accelerated large-scale renewables target, a holistic review of projected trans-Mediterranean grids and their market, technical, and financial obstacles of implementation was conducted. For south- and east-shore countries, major legal and regulatory barriers encompassing non-liberalized market structure, regulation gaps of taxation and transmission tariffs, and the private sector’s access rights need to be removed. Enhancement of domestic grids, substations, and harmonized grid codes and frequency, voltage, and communication technology standards among all trans- Mediterranean countries are physical prerequisites for implementing the Trans-Mediterranean Electricity Market. In addition, the mobilization of capital instruments along with private and international investments is indispensable for the realization of supranational transmission projects. As the final section of the decarbonization roadmap, the development of electric appliances, equipment, and vehicles with higher efficiency is inevitable in the decarbonized building, transportation, and industry sectors.